A critical review addressing drilling-induced damage of CFRP composites. (15th August 2022) - Xu, Jinyang; Yin, Youkang; Paulo Davim, J.; Li, Linfeng; Ji, Min; Geier, Norbert; Chen, Ming
Abstract: Carbon fiber reinforced polymers (CFRPs) have been extensively used in diverse industrial fields owing to their superior properties and excellent functions. Mechanical drilling has become a compulsory operation to shape these composites to target dimensions and desired quality for assembly purposes. Cutting-induced damages are critical issues when dealing with the manufacturing of CFRPs as they adversely affect the performance and acceptance of eventually-machined composite parts. In this paper, a critical review has been conducted to offer a comprehensive understanding of drilling-associated damages for CFRPs by focusing on illustrating the damage formation mechanisms, classification, evaluation, and suppression. Recent advances addressing the damage issues in drilling CFRPs are also carefully reviewed by critically analyzing the scientific findings reported in the open literature. The fundamental effects of the fiber layup, process parameters, tool geometries/materials, cutting environments and process strategies on the formation and progression of composite damage are discussed. The article also outlines potential solutions and strategies to suppress the formation of drilling-induced damages for CFRP composites. Both researchers and manufacturers will benefit from this review article as they seek to achieve damage-free drilling of CFRP composites.